Pestalotia Leaf Spot and Fruit Rot of Strawberry - Juliana S. Baggio; Natalia A. Peres (EDIS)
Pestalotiopsis-like fungi cause diseases on many different species of plants worldwide, including strawberry. The pathogen is not necessarily new to strawberry and was first reported causing fruit rot in Florida and Israel in the 1970s. However, during the 2018–19 and 2019–20 strawberry seasons, severe and unprecedented outbreaks were reported in Florida, characterized by symptoms on nearly all plant parts including roots, crowns, petioles, fruit, and leaves. This new 4-page publication of the UF/IFAS Plant Pathology Department describes the disease and its causal agent and briefly covers what is known about disease development and control practices. This document will provide valuable information to strawberry nursery and fruit production growers. Written by Juliana S. Baggio and Natalia A. Peres. https://edis.ifas.ufl.edu/pp357